Effects of Interfacial Charges On Doped and Undoped HFOX Stack Layer with Tin Metal Gate Electrode For Nano-Scaled CMOS Generation - S. Chatterjee; Y. Kuo (Журнал нано- та електронної фізики)
A comparison of the interfacial charges present in the high-k stacked gate dielectrics for Zr-doped HfOx and undoped HfOx samples with titanium nitride (TiN) metal gate electrode is reported here. The metal gate work function value (4.31 eV) for TiN gate electrode was extracted from the TiN/SiO2 /p-Si capacitor. The calculated charge densities in both doped and undoped films are of the order of 1012 cm – 2. The interfacial charge present in the high-k/SiO2 interface is negative for ALD deposited pure HfO2 samples; where as the charges are positive for RF-sputter deposited pure HfO2 and Zr-doped HfOx samples. The existence of positive interface charges may be due to the fabrication process.